EFFECT OF OBSTACLE IN RIVER ON THE HEAT DISSIPATION OF HOT WATER INJECTION (Journal of Engineering, 2009)
Numerical analysis of the cooling process of hot water discharge from a steam power plant into a river has been carried out in the present study. A mathematical model describing the flow field and temperature distribution induced in the river as a result of the cooling process is made based upon the assumptions of steady state, two-dimensional, turbulent flow, in the horizontal plane. The governing equations are the continuity, the momentum, the (К-ε) turbulence model and the energy equation. A proper initial and boundary condition are specified to be used in the solution of the governing equations. A numerical solution of the governing equations is made by using the control volume approach, with non-staggered grid technique and modified SIMPLE algorithm. The numerical solution is capable of calculating the velocity and temperature distributions of the calculation domain. The numerical results show that the developed algorithm is capable of calculating the flow field, properly and accurately. Results are obtained for ten cases of configuration, constant aspect ratio and weather conditions for Baghdad. The results show that the injection velocity effect on the temperature distribution and stream line , the exist of obstacle and its distance from the injection zone but the increase in injection temperature cause a small effect on temperature distribution and stream line.